2014
DOI: 10.1371/journal.pone.0084993
|View full text |Cite
|
Sign up to set email alerts
|

Serotype and Genotype Distribution among Invasive Streptococcus pneumoniae Isolates in Colombia, 2005–2010

Abstract: In Colombia, a laboratory-based surveillance of invasive Streptococcus pneumoniae isolates as part of SIREVA II PAHO has been conducted since 1994. This study describes the serotype distribution, antimicrobial resistance, and genetic relationships of pneumococcal isolates recovered in Colombia from 2005 to 2010. In this study, demographic data of invasive S. pneumoniae isolates were analyzed, and antimicrobial susceptibility patterns were determined. Pulse field gel electrophoresis (n = 629) and multilocus seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
2
12
0
1
Order By: Relevance
“…It is also very important to point out the circulation of Colombia 23F -26 clone, ST338. This clonal group has also been reported in several countries [ 30 , 36 , 37 ]. Apart from these three clonal groups, the specific clonal structure of the PNSSP isolates was dominated by a few other clones (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is also very important to point out the circulation of Colombia 23F -26 clone, ST338. This clonal group has also been reported in several countries [ 30 , 36 , 37 ]. Apart from these three clonal groups, the specific clonal structure of the PNSSP isolates was dominated by a few other clones (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…In Asian countries invasive pneumococcal isolates remained highly resistant to macrolides, tetracycline, and TMP-SXZ each year [ 27 ]. In this study setting, we found a lower proportion (0.6 %) of isolates resistant to erythromycin in comparison with developed countries [ 28 , 29 ] other Latin American countries [ 30 ] and wealthier regions within Brazil [ 31 ]. This may be due to the relatively high cost of macrolides, which limits its use in clinical practice in low income population settings.…”
Section: Discussionmentioning
confidence: 77%
“…Subsequently, in 2010, the PCV10, which includes the seven serotypes of PCV7 and serotypes 1, 5 and 7F, was introduced (5). The benefits of introducing PCVs have been demonstrated by the high efficacy against vaccine serotypes (VT) in invasive diseases and in carriage (6).…”
Section: Conclusión Los Clones Colombiamentioning
confidence: 99%
“…According to the United States Active Bacterial Core Surveillance, in 2010, the incidence of IPD in ≥ 65 year old adults was 36.4 cases per 100,000 [1]. In Latin America, it is estimated that every year, IPD is responsible for up to 28,000 deaths, 182,000 hospitalizations, and 1.4 million outpatient consults [2]. Annually, more than 10 billion dollars are expended in healthcare-associated costs in the United States alone due to IPD.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pneumococcal infections have been considered as a public health care problem. Importantly, mortality due to IPD in adults has remained steady even after the extensive usage of broad-spectrum antibiotics and better vaccination coverage in children [2][3][4].…”
Section: Introductionmentioning
confidence: 99%